STRATEGI PENINGKATAN REMMITANCE MALALUI PENGIRIMAN TENAGA KERJA INDONESIA KE LUAR NEGERI ASAL PROVINSI JAWA TIMUR, TAHUN 2008-2013 - Adhania Hexxa Yuniar (Perpustakaan Universitas Surabaya, 2015)
This research investigates the the strategy of increasing remmitance through Indonesian labor originated from province of East Java. The research was conducted using the SWOT analysis under four steps, namely assessing the strength, weakness, opportunities and threat. The method of this research is a qualitative approach the key strategy for increating remmitance descriptive. The main result of this research indicates that is to expand employment opportunities, improve quality, and enhance productivity of labors origined from East Java.